Molecular detection of Trichomonas Vaginalis using 5.8S rRNA gene in reproductive-age women in Erbil city - M. Jabbary, Hawri; Ismail Hassan , Zuber; Mohammad Ismael , Hero (Zanco Journal of Medical Sciences (ZJMS), 2026)
Background and objective: Trichomoniasis is a parasitice infection that impacts the human reproductive and urinary systems, constituting a significant non-viral sexually transmitted infection globally. The study evaluated the 5.8S rRNA gene as a molecular target for diagnosing T. vaginalis infection among reproductive-age women in Erbil city. Methods: Vaginal swabs and urine samples from 800 women were examined microscopically and by PCR targeting a 368 bp fragment of the 5.8S rRNA gene. Results: Thirteen samples (1.63%) tested positive microscopically and were all confirmed by PCR, demonstrating 100% sensitivity and specificity. All patients with positive microscopic identification were confirmed using the amplification of a 368bpfragment of 5.8S rRNA gene, acquisition of the accession number from the gene bank (NCBI) under accession numbers (PV935463, PX147457, PX147458, PX147459, PX147460, PX147461, PX147462, PX147463, PX147464, PX147465, PX147466, PX147467, PX218319). Conclusion: Molecular detection targeting the 5.8S rRNA gene offers a highly sensitive and specific diagnostic tool for Trichomonas vaginalis, supporting its use alongside microscopy to improve detection accuracy in clinical settings.